Futures Thinking for Culturally Grounded Problem-Solving: Reimagining Sustainable Bali Tourism through Local Knowledge - Chunta Chiu; I Nyoman Laba Jayanta; I Wayan Suantara (Indonesian Journal of Educational Research and Review, 2026)
Students’ limited creative thinking and problem-solving skills require higher education to develop pedagogical approaches that are future-oriented, contextual, and culturally grounded. This study explored how a futures thinking approach deepened university students’ engagement with local knowledge and strengthened their problem-solving skills through the “Future Bali Travel in 2034” project. A qualitative action research design was employed with ten pre-service teacher education students at Universitas Pendidikan Ganesha. Data were collected through semi-structured interviews, reflective notes, learning artifacts, and student project outputs, then analyzed using thematic analysis. The findings showed that students developed a broader understanding of futures thinking as a way to imagine alternative futures, anticipate change, and design adaptive responses. Students also reinterpreted Balinese local knowledge as a living resource for sustainable tourism innovation. Project outputs demonstrated students’ ability to integrate cultural preservation, digital innovation, environmental awareness, and community empowerment into future tourism scenarios. The study concludes that integrating futures thinking, local knowledge, and project-based problem-solving can support anticipatory, culturally responsive, and transformative learning in higher education.